Phenomenology of Coping Strategies and Stress Among High School Adolescents - Kurniawaty, Yuni; Veronica Silalahi; Sri Winarni; Ni Luh Agustini Purnama; Baswara Yua Kristama (Technium Social Sciences Journal, 2024)
Stress cannot be avoided even by a teenager in high school. Some people use coping strategies to reduce stress. Coping strategies allow for more targeted and effective psychological interventions and will increase a person’s ability to manage stress. The aim of this research is to analyze adolescents’ coping strategies and stress. This research is a type of qualitative research using phenomenological methods. Research location High school. Determining research topics is inherently a snowball. The informants for this research were high school adolescents, teachers, and parents. The primary data collection technique involves conducting in-depth interviews using multiple informant interview guidelines. The process of data analysis includes: data reduction, data categorization, synthesis and ends with the development of a working hypothesis. Research findings revealed that adolescents are always stressed because stressors are always present in their lives. Internal and external sources of stress in adolescents have been found. Internal drivers of adolescent stress such as temperament, attachment, mastery, and self-determination processes. External factors observed in adolescents are social conditions, parental models and school processes. Several types of adolescent coping strategies have been shown to be adaptive and maladaptive. Adaptive coping strategies include reflection and self-reflection. Maladaptive coping strategies have been found to involve avoiding problems. Socialize to adolescents, parents and schools how to know adolescents better and help them in the developmental phase of searching for their own identity. The help of parents and stakeholders such as the school community is very important in this matter.